Implementation of a conversational club for the improvement of oral communication of english in students with level A1 - León Bravo, Anahis Yamileth (Machala : Universidad Técnica de Machala, 2021)
This research focuses on improving oral communication of English in students with A1 level of the Escola de Idiomas institute through a conversational club based on the communicative approach. In addition, it is intended to demonstrate that the application of effective didactic strategies in the planning of English classes will significantly improve the communication skills of students. The reviews of studies carried out support that a conversational club is an interactive space, which allows the ideas and arguments of the participants to flow spontaneously, also that it will develop satisfactorily when effective teaching strategies are applied to it. The research is qualitative in nature with an action-research approach. The instruments applied for data collection were participant observation, interview, the pedagogical test and checklist. Likewise, the intervention proposal contains speaking activities aimed at students, with the aim of improving their oral communication.
Esta investigación se centra en mejorar la comunicación oral del inglés en estudiantes con nivel A1 del instituto Escola de idiomas a través de un club conversacional fundamentado en el enfoque comunicativo. Además, se pretende demostrar que la aplicación de estrategias didácticas efectivas en la planificación de las clases de inglés, mejorará significativamente las competencias comunicativas de los estudiantes. Las revisiones de estudios realizados sustentan que un club conversacional es un espacio interactivo, el cual permite que las ideas y argumentos de los participantes fluyan con espontaneidad, asimismo que este se desarrollará satisfactoriamente cuando estrategias didácticas efectivas sean aplicadas al mismo. La investigación es de carácter cualitativa con un enfoque de investigación- acción. Los instrumentos aplicados para la recolección de datos fueron la observación participante, entrevista, prueba pedagógica y una lista de cotejo. Asimismo, la propuesta de intervención contiene actividades de speaking dirigidas a estudiantes, con el objetivo de mejorar su comunicación oral.
Keywords: STRATEGY; DIDACTIC; COMMUNICATION; CONVERSATIONAL